Development of Calcium Phosphate Cements for Bone Repair: An Overview Based on Patent Analysis - Khalid Khairoun; Abdellah Laazizi; Ahmed Fatimi (Materials Proceedings, 2023)
The development of calcium phosphate cement (CaPC) has been regarded as a significant advance in the field of bone defect reconstruction. This patent analysis-based research concerns patent documents with an active legal status until 2022. The state of the art is reviewed by introducing what has been patented concerning CaPCs for bone repair. As a result, 740 active patent documents were found, and 51% of them were published during the last 7 years. According to the findings, the United States ranked as the first jurisdiction, with academic institutions from France and the United States leading the patenting way. The Cooperative Patent Classification reveals that most inventions are intended for materials or treatments for tissue regeneration, such as the reconstruction of bones with weight-bearing implants, as well as inorganic materials for grafts or prostheses, such as phosphorus-containing materials.